2018
DOI: 10.1177/1057083717750078
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Cooperating Music Teachers on Service Motives, Relationships, and Mentoring Strategies During Student Teaching

Abstract: The purpose of this qualitative study was to examine the perceptions of four cooperating teachers concerning their role in the music student teaching experience. Participants included an elementary music educator, middle school band director, high school band director, and a high school choir director. Research questions were (a) What are the personal and professional motivations for hosting a student teacher? (b) How do cooperating teachers describe relationships with student teachers? and (c) What strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 17 publications
1
19
0
2
Order By: Relevance
“…First, cooperating teachers’ experiences matched common definitions of professional development, although these experiences were not identified as a benefit of or motivation for hosting a student teacher. Participants in Palmer’s (2018) study cited enhanced reflection of their own teaching and confirmation of their knowledge and understanding, supporting that hosting a student teacher may be viewed as a form of professional development. Second, compared to the commonly held view that professional development is an event or a one-shot experience, in the context of this study, cooperating teachers perceived hosting a student teaching placement as an extended form of professional development.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…First, cooperating teachers’ experiences matched common definitions of professional development, although these experiences were not identified as a benefit of or motivation for hosting a student teacher. Participants in Palmer’s (2018) study cited enhanced reflection of their own teaching and confirmation of their knowledge and understanding, supporting that hosting a student teacher may be viewed as a form of professional development. Second, compared to the commonly held view that professional development is an event or a one-shot experience, in the context of this study, cooperating teachers perceived hosting a student teaching placement as an extended form of professional development.…”
Section: Discussionmentioning
confidence: 72%
“…The supervisor, student teacher, and cooperating teacher work hand-in-hand to organize assignments, teaching schedules, and all related experiences as a form of action research, thereby collaboratively bridging the gap between theory and practice. Cooperating teachers also may be invited to campus by the university supervisor to participate in meetings focused on revision of music teacher education curricula, sessions focused on becoming a more effective student teacher mentor, or other professional development events designed for experienced teachers (Berg & Rickels, 2018; Burton & Greher, 2007; Conkling, 2007; Morin, 2000; Palmer, 2018; Zemek, 2008). Hosting and mentoring student teachers may serve as an alternative form of professional development, as student teachers may help cooperating teachers stay current with new developments in the field (Palmer, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Palmer (2018) investigated four experienced cooperating music teachers’ perceptions of their roles in student teaching based on two individual interviews and one focus group interview. Palmer found that cooperating music teachers valued their co-teaching experiences with student teachers.…”
Section: Views Of Co-teachers Concerning Their Co-teaching Experiencesmentioning
confidence: 99%
“…Draves (2008) found the cooperating music teachers in her study wanted to collaborate with their student teachers equitably in all aspects of teaching. Cooperating music teachers have been found to recognize the importance of creating the practicum environment grounded in collaborative relationships with student teachers (Draves, 2008; Palmer, 2018). Veal and Rikard (1998) noted that special-subject teachers, including music teachers, could benefit from collaborative work with student teachers.…”
mentioning
confidence: 99%